At Home in Blackness: How I Became Black - Etoroma, Efa E. (Qualitative Sociology Review, 2010)
I became and have remained Black in Canada by interacting with Blacks. Altercasting (the “push” from the larger society) moved me into interacting intentionally with Blacks, interacting with Blacks helped make me Black by immersing me in the Black experience, and studying Blacks helped anchor me within the Black community by giving me an understanding of what it means to be Black. In this paper, which is based on autoethnography, I offer a brief overview of the concept of Blackness in Canada and then I discuss the key ways in which my Black identity was developed and is sustained. The key mechanisms discussed are altercasting, interacting with Blacks, and studying the Black community.